The Effectiveness of Zinc Micronutrients From Pumpkin (Cucurbita moschata D) Extract on the Testosterone Levels of Mice (Mus musculus L) - Risa Purnamasari; Nova Lusiana; Linda Prasetyaning Widayanti; Mei Lina Fitri Kumalasari (Indian Journal of Forensic Medicine & Toxicology, 2022)
Various factors cause disharmony in the household. One of them is erectile dysfunction. This can be treated by providing aphrodisiacs and some minerals such as zinc to increase libido. One of the plants that contain zinc is pumpkin (Cucurbita morchata D ). This study was conducted to determine the differences in giving pumpkin skin, meat, and seed extracts to testosterone levels. This study uses a laboratory experimental research type. This study, using extract variables from the skin, meat and seeds of pumpkin (Cucurbita moschata D) and levels of the hormone testosterone. The sample used was male mice (Mus musculus) divided into control groups and three treatment groups. Data were analyzed using the One-way ANOVA statistical test.There were differences in testosterone levels in mice between the control group and the group of mice given extracts of meat, skin and seeds (p-value <0.05).The highest testosterone level in mice was in mice given pumpkin seed extract.